Gwarowy leksem gryfny jako modny komponent kultury konsumpcyjnej - Łuc, Izabela (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The object of the analysis is the way of creating commercial utterances and functional names in which the formal indicator is the dialectal lexeme gryfnie recognized as a fashionable component of Polish language of consumption. According to the communicative practice of the creators of cultural texts, the use of the gryfny component valorizes products, identifies service objects, assesses offers and highlights the speakers of the language living in the Upper Silesia region. The analytical material coming from the advertisements spread by media and on the Internet was described from the perspective of cultural linguistics and pragmalinguistics. The references to cognitive conception of meaning fields were made taking into account the appropriate methodological solutions and the complex polisystem of commercial conditions.